Age Related Histological and Histochemical Studies on the Tubuli Recti, Rete Testes and Mediastinum Testis in Assam Goat (Capra hircus) - Sarma, Kamal; Kalita, S. N.; Devi, Jonali (Indian Journal of Veterinary Anatomy, 2015)
A total of eighteen male Assam goats were used in this study to record the histology and histochemistry of the tubuli recti, rete testis and mediastinum testis. The sections were cut and stained with was located at the centre of the testis in the goats of all the age groups. The rete channels had a distinct tubular lumen from birth. The reticular fibres formed network in the mediastinum testis and proceeded towards the rete testis. The basement membrane of tubuli recti and rete testis showed moderate to strong reaction for basic proteins in all the age groups, but showed moderate PAS reaction.